Pola Umum Wacana Berita Duka Berbahasa Prancis dan Berbahasa Indonesia - Rachmawati, Jeanni Imas; Andriani, Merry (Universitas Negeri Semarang, 2024)
This study analyzes the general pattern of discourse of French and Indonesian death notices. The researcher used 20 death notices consisting of 10 French death notices and 10 Indonesian death notices obtained from the internet. This research is a mixed research which is qualitative-descriptive and quantitative. The data collection technique used listening and note-taking technique. Meanwhile, the data analysis was carried out using the theory of genre analysis according to Swales and the category of the percentage of occurrence of moves that compose each death notices according to Pho. Based on the results, it is found that there are three obligatory moves which are also the general pattern of French death notices namely 7-3-4; Showing the Mourner, Providing Explanation, and Showing the Profile of the Deceased. On the other hand, only two obligatory moves were found to be the common pattern of Indonesian death notices namely 3-4; Giving Explanation, Showing the Profile of the Deceased. Understanding the pattern of death notices.is one of the methods to explore a culture because it can be seen how a cultural variation organizes and presents information.